Taṣawwur Mu‘allimī Al-Lughah Al-‘Arabiyyah fī Taṭbīq Al-Manhaj Al-Mustaqill fī Bantan - Salim, Irfan; Daniyah, Dede Nur Ufi (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study aims to identify Arabic language teachers' views regarding the implementation of an independent curriculum to instruct Arabic in Banten. These include teachers' awareness, acceptability, and assessment of the curriculum, and the factors and barriers faced in its implementation. Under a qualitative descriptive design, data were collected via observations, open-ended questionnaires, interviews, and documents. The results indicate that teachers' attitudes are positive and cooperative in general. Although there are some variations in comprehension and readiness, most teachers appreciate the independency and usability of the independent curriculum, especially regarding providing space for creativity and contextualization. Training experience, initiative on the part of individuals, support from the school principals, and accessibility of facilities are found to be the factors contributing to successful implementation. Nevertheless, it is limited by limited teaching hours, differences in the backgrounds of students, low learning motivation, and a lack of special preparatory training to instruct the Arabic language. In overcoming these, teachers employ creative teaching approaches and improve on teamwork among themselves. The initiative is to be applied as a point of reference for policymakers, schools, and teachers to further enhance the implementation of the independent curriculum in Arabic language instruction.